The Importance of Steroid Uptake and Intracrine Action in Endometrial and Ovarian Cancers - Rižner, Tea Lanišnik; Thalhammer, Theresia; Özvegy-Laczka, Csilla (Frontiers in Pharmacology, 2017)
Endometrial and ovarian cancers predominately affect women after menopause, and are more frequently observed in developed countries. These are considered to be hormone-dependent cancers, as steroid hormones, and estrogens in particular, have roles in their onset and progression. After the production of estrogens in the ovary has ceased, estrogen synthesis occurs in peripheral tissues. This depends on the cellular uptake of estrone-sulfate and dehydroepiandrosterone-sulfate, as the most important steroid precursors in the plasma of postmenopausal women. The uptake through transporter proteins, such as those of the organic anion-transporting polypeptide (OATP) and organic anion-transporter (OAT) families, is followed by the synthesis and action of estrogen E2. Here, we provide an overview of the current understanding of this intracrine action of steroid hormones, which depends on the availability of the steroid precursors and transmembrane transporters for precursor uptake, along with the enzymes for the synthesis of E2. The data is also provided relating to the selected transmembrane transporters from the OATP, OAT, SLC51, and ABC-transporter families, and the enzymes involved in the E2-generating pathways in cancers of the endometrium and ovary. Finally, we discuss these transporters and enzymes as potential drug targets.